Parents' Weekend reception in the Alumnae Lounge, including a performance by the a capella group Essence. Photo 050 - Leonard, Spencer (Tufts Archival Research Center, 2008)
Parents' Weekend reception in the Alumnae Lounge, including a performance by the a capella group Essence.